Specification and positioning of the anterior neuroectoderm in deuterostome embryos. Issue 3 (6th March 2014) - Range, Ryan; McClay, David; Ettensohn, Charles
Summary The molecular mechanisms used by deuterostome embryos (vertebrates, urochordates, cephalochordates, hemichordates, and echinoderms) to specify and then position the anterior neuroectoderm (ANE) along the anterior–posterior axis are incompletely understood. Studies in several deuterostome embryos suggest that the ANE is initially specified by an early, broad regulatory state. Then, a posterior‐to‐anterior wave of respecification restricts this broad ANE potential to the anterior pole. In vertebrates, sea urchins and hemichordates a posterior–anterior gradient of Wnt/β‐catenin signaling plays an essential and conserved role in this process. Recent data collected from the basal deuterostome sea urchin embryo suggests that positioning the ANE to the anterior pole involves more than the Wnt/β‐catenin pathway, instead relying on the integration of information from the Wnt/β‐catenin, Wnt/JNK, and Wnt/PKC pathways. Moreover, comparison of functional and expression data from the ambulacrarians, invertebrate chordates, and vertebrates strongly suggests that this Wnt network might be an ANE positioning mechanism shared by all deuterostomes. genesis 52:222–234. © 2014 Wiley Periodicals, Inc.